Does Entrepreneurs’ Darwinian Social Identity Contribute to Business Performance via Corporate Social Responsibility in China? The Role of Entrepreneurs’ Well-Being - Chen, Jinliang; Chen, Ning Chris; Yu, Kangkang; Hall, Colin Michael (Frontiers in Psychology, 2021)
Although the impact of social identity on successful entrepreneurship has attracted much scholarly attention, it is often to evaluate successful entrepreneurship through financial performance. Recently, there is a growing body of researches beginning to pay attention to the impact of entrepreneur’s identity on corporate social responsibility (CSR) regarded as social aspect of successful entrepreneurship. However, little is known regarding how entrepreneurs’ Darwinian identity affect CSR. This study addresses this issue by combining stakeholder theory with social identify theory, to investigate the relationship between entrepreneurs’ Darwinian identity and business performance via CSR. In addition, the moderating effect of entrepreneur’s well-being is further examined to uncover the interaction between the personal outcomes and firm outcomes. The empirical results indicate that entrepreneurs’ Darwinian identity contributes positively to CSR, so as further to business performance. In addition, this relationship is further found to be significantly moderated by entrepreneurs’ well-being. The results indicate that entrepreneurs can achieve business success via CSR, by which entrepreneurs can further acquire successful entrepreneurship through caring more about their well-being.